Delta Neutrophil Index and C-Reactive Protein as Predictors of Mortality in Early Onset Neonatal Sepsis at Dr. Moewardi Hospital - Deaneva, Almira Muthia; Siregar, Rustam; Martuti, Sri (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Neonatal sepsis is an infection disease in newborns that still be a major problem in developing countries such as Indonesia. Early onset sepsis has higher mortality and morbidity. A simple and applicable biomarkers are needed to predict mortality in early onset neonatal sepsis. This study aimed to investigate whether Delta Neutrophil Index (DNI) and C-Reactive Protein (CRP) can be used as predictors of mortality in early onset neonatal sepsis. Subjects and Method: A cohort study that was conducted at neonatal HCU and NICU at Dr. Moewardi Hospital from March to June 2023. Total of 30 neonates aged 0-72 hours which met the inclusion criteria and became research subjects. The dependent variable was the mortality of neonatal sepsis. The independent variable were levels of DNI and CRP values. The instruments were flowcytometry to measure levels of DNI and Enzyme Linked Immunoassay (ELISA) for determining CRP values. Data were analyzed using SPSS 25.0. Bivariate analysis was using Chi square and Fisher exact followed by multivariate analysis using logistic regression with p<0.05. Results: Thirty early onset septic neonates were included in study, of whom 17 children died and 13 children survived. Both DNI and CRP had significant correlation with mortality of neonatal sepsis (p<0.001). The DNI cut-off value of ≥ 5.4% (OR = 10.83; 95% CI 1.96 to 59.63; p = 0.004) can predict mortality in early onset neonatal sepsis. The CRP cut-off values of ≥5.75 mg/L (OR = 15.56; 95%CI 2.59 to 93.57; p = 0.001) could predict early onset neonatal sepsis mortality. Other factors such as gender, gestational age, birth weight and blood culture couldn’t be used as predictors of mortality in neonatal sepsis, with p value >0.05. Conclusion: DNI and CRP could be used as predictors of mortality in early onset neonatal sepsis.